Pengaruh Good Corporate Governance dan Kinerja Lingkungan Terhadap Kinerja Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Syanisyah Andini (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of Good Corporate Governance (GCG) mechanisms, proxied by the Board of Commissioners and Audit Committee, as well as Environmental Performance on Financial Performance in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. The research method used is quantitative, with a purposive sampling technique that resulted in 22 companies as samples, totaling 88 observations over the four-year study period. The research data is secondary data obtained through financial statements and annual reports from the official IDX website. Literature reviews indicate inconsistencies in previous studies; however, the hypothesis of this research suggests that the Board of Commissioners, Audit Committee, and Environmental Performance have a positive and significant effect on the company's financial performance. The board of commissioners and audit committee play a role in strengthening the oversight function to minimize agency costs and improve efficiency. Meanwhile, good environmental performance, measured through PROPER ratings, is expected to enhance the company's positive image in the eyes of investors and stakeholders.